CpG-oligodeoxynucleotides exert remarkable antitumor activity against diffuse malignant peritoneal mesothelioma orthotopic xenografts. Issue 1 (December 2016) - De Cesare, Michelandrea; Sfondrini, Lucia; Pennati, Marzia; De Marco, Cinzia; Motta, Valentina; Tagliabue, Elda; Deraco, Marcello; Balsari, Andrea; Zaffaroni, Nadia
Abstract Background Diffuse malignant peritoneal mesothelioma (DMPM) is a rare and locally aggressive disease. DMPM prognosis is dismal, mainly due to the lack of effective treatment options and the development of new therapeutic strategies is urgently needed. In this context, novel immunotherapy approaches can be explored in an attempt to improve DMPM patients' survival. Methods We tested the efficacy of CpG-oligodeoxynucleotides (CpG-ODN), synthetic DNA sequences recognized by Toll-like receptor 9 and able to induce innate/adaptive immune response, in two DMPM orthotopic xenografts (MesoII and STO), which properly recapitulate the dissemination pattern of the disease in the peritoneal cavity. Severe combined immunodeficiency mice carrying DMPM xenografts were treated at different stages of tumor development with i.p. delivered CpG-ODN1826 for 4 weeks. CpG-ODN1826-induced modulation in the composition of peritoneal immune infiltrate was assessed by flow cytometry. Results When administered to early-stage tumors (i.e., 4 days after i.p. DMPM cell injection in mice), the agent exhibited impressive efficacy against MesoII by completely inhibiting tumor take and ascites development (no evidence of tumor masses and ascites in 6/6 mice at necropsy), and also impaired STO tumor take and growth (4/6 tumor-free mice; i.p. tumor masses reduced by 94 % in the 2 remaining mice, P  = 0.00005). Interestingly, when tested against late-stage STO tumors (i.e., 11 days after i.p. DMPM cell injection in mice), CpG-ODN1826 was still able to reduce the growth of i.p. tumor masses by 66 % (P  = 0.0009). Peritoneal washings of tumor-bearing mice revealed a strong increase of macrophage infiltration together with a decrease in the presence of B-1 cells and a reduced IgM concentration after CpG-ODN1826 treatment. Conclusions Our results indicate that locally administered CpG-ODN1826 is able to markedly affect the growth of both early- and late-stage DMPM orthotopic xenografts in the absence of severe side effects, and suggest a possible clinical role for the agent in the therapy of DMPM.